Revisiting the Relationship Between the Strength of Environmental Regulation and Foreign Direct Investment - Bae, Moon Gyu; Wang, Yi Chen; Liu, Na (Frontiers in Psychology, 2022)
Interest in sustainability is increasing, and research on ESG management continues. The first issue to be discussed in the present situation is the environment. The study between the environment and internationalization was conducted around two conflicting arguments. First, the pollution haven hypothesis states that multinational corporations move to countries with looser regulations depending on environmental regulation. Next is the Porter hypothesis, which argues that well-designed environmental regulations offset the cost of compliance and ultimately help firms gain a competitive advantage through innovation that enhances performance. However, the two arguments have not yet reached a consensus conclusion. In addition, studies on the national level and studies considering the distance between countries, an important factor in international management, are lacking. This paper aims to revisit the relationship between the strength of environmental regulation and FDI in the context of increasing environmental concerns. And the effect of the relationship between country distance and environmental regulations, which existed as a limitation of previous studies, on FDI is examined.